Cannabis Use Disorder in Young Adults with Acute Myocardial Infarction: Trend Inpatient Study from 2010 to 2014 in the United States - Patel, Rikinkumar S (Cureus, 2018)
Objective This study determines the trend of acute myocardial infarction (AMI) in cannabis users. Demographic characteristics, hospitalization outcomes, and utilization of primary treatment modalities were evaluated in AMI inpatient population. Methods The study used data from the nationwide inpatient sample (NIS) for the years 2010-2014. We identified patients with AMI as the primary diagnosis (N = 379,843) and patients with cannabis use disorder as the secondary diagnosis. We used Pearson’s chi-square (χ2) test and independent sample t-test for measuring the categorical and continuous data, respectively. Results Inpatient admissions for AMI among cannabis users increased by 32% (P = 0.001). The overall mean age of cannabis users with AMI (41 years) remained stable with no significant differences observed across age groups. AMI was predominant in male cannabis users (79.1%), and there was a 38.3% increase in the prevalence in female cannabis users over five years (P < 0.001). About one-third of the cannabis users with AMI were covered by medicaid with a 70.5% pike (21% in 2010 to 37.5% in 2014; P < 0.001). There was a strong linear trend in nonelective admissions for AMI in cannabis users (P = 0.003) along with a moderate-to-severe morbidity (P = 0.001). Mean length of inpatient stay had a decreasing linear trend (P = 0.003), whereas hospitalization costs were increasing (P = 0.024), averaging $65,879 per admission for AMI. Cannabis users had a strong linear increasing trend (P = 0.007), with a 60% increase in in-hospital mortality (1.0% in 2010 to 1.6% in 2014). Conclusion Due to the risk of AMI, as seen in numerous case reports, the trend of emergency admission and severe morbidity due to AMI in cannabis users is also increasing. Also, cannabis users have a higher healthcare cost to manage AMI, yet the in-hospital mortality has risen tremendously over the last few years. It is imperative to know that chronic cannabis worsens the outcomes in AMI patients, and more clinical studies are needed to show the association of episodic use in cannabis abusers and AMI.